Penguatan Masyarakat Konsumen Abad ke-21: Studi Kasus Konsumerisme Fast Fashion di Inggris - Humaira, Humaira; Fitriani, Evi (Paradigma: Jurnal Kajian Budaya, 2021)
This article aims to understand the development of fashion consumerism in the United Kingdom (UK) with the focus: why fast fashion consumerism in the last two decades was very high? This study applied a post-structuralism paradigm, namely the Libidinal Economy concept from Jean-Francois Lyotard and a post-modernism paradigm on the Consumer Society from Jean Baudrillard. The method employed in the article is a case study in the UK in the last two decades. Data were collected from scientific writings, documents, news, and advertisements in media. The results show that fashion consumerism in the UK dated back to the 18th century; it strengthened in the first two decades of the 21st century, driven by libidinal economic activities and facilitated massively by technological advancements in both marketing and trades. The ability of multinational fast fashion companies to utilize the mass media to construct the social status of its consumers and to create “hyper-reality” needed by modern people nowadays seemed to surpass the awareness of British clothing consumers regarding the environmental impacts and global imbalances of the fast fashion industry. In this study, the application of the post- structuralism paradigm clarifies the relationship between technology, mass media, the expansion of capitalism and the consumption of fast fashion in British society, whereas the post-modernism paradigm highlights socio-cultural aspects that encouraged the creation of hyper-reality through fast fashion among the British. These findings contribute to the knowledge about the relationship between technology, media, and multinational fast fashion companies with the development of consumer society in the UK.